Hybridity as Reflected in Fabiola in Ibi Zobo’s American Street Novel (EUFONI: Journal of Language, Literary, and Cultural Studies, 2022)
This study examines the depiction of hybridity and mimicry in Ibi Zoboi's novel "American Street," focusing on their effects on the protagonist, Fabiola. Titled "Hybridity as Reflected in Fabiola in Ibi Zoboi’s American Street," the research explores how Fabiola's move to America initiates her hybrid identity and her adoption of American culture. Using a qualitative method, the study employs Homi K. Bhabha's (1990) theories of hybridity and mimicry to analyze the novel. The findings reveal that Fabiola embodies both hybridity and mimicry through her adaptation to American language, behavior, and attire. The study also highlights the impacts of hybridity and mimicry on Fabiola, such as culture shock, identity crisis or ambivalence, and camouflage.